Penggunaan Discovery Learning Berbantuan Laboratorium Virtual pada Penguasaan Konsep Fisika Siswa - Putri Iman Sari; Gunawan Gunawan; Ahmad Harjono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
Discovery learning is a way of teaching that gives students the knowledge to construct a concept discovered through an experiment. The implementation of the experiment will be more effectively done by utilizing the media realized in computer technology, one of which uses virtual laboratory. This study aims to improve students' mastery of concepts of physics discovery aided by the application of learning virtual lab. The results showed that the increase in student mastery of concepts taught Using discovery learning assisted higher laboratoium more than the students who are not being treated. Mastery of concepts in each sub-material has increased significantly, except in the concept of electrical measuring instrument control group is superior to 1% compared to the experimental group.